(untitled) (International Journal of Food and Nutritional Sciences, 2022)
POSCO ACT is a National Women’s safety act; the POSCO ACT has become a hugely important empowerment tool for women in the state. The statement of the problem was a study to assess the effectiveness of SIM on knowledge regarding POSCO ACT among young women and to determine the association of POSCO ACT with selected demographic variables